Evaluating the Scale-Readiness and Efficiency-gains of Small Farmers Large Field (SFLF) in Potato-based cropping systems: A Case Study from Nalanda, Bihar - Janakiraman, Deepa; Veettil, Prakashan Chellattan; Ali, Shahid; Krupnik, Timothy J. (TAFSSA, 2024)
This study evaluates the scale-readiness and efficiency gains of the Small Farmer Large Field (SFLF) model implemented in potato-based cropping systems in Nalanda district, Bihar, during 2022-24. The research, based on focus group discussions (n=23) and key informant interviews (n=61), assessed the model's operational efficiency, implementation effectiveness, and scaling potential. Results indicate yield improvements of 30-35% and input cost reductions of 10-15% among participating farmers. The model achieved an innovation-readiness score of 6 (semi-controlled testing) but a use-score of 1 (single-institution implementation), highlighting reliance on a single organization for implementation. While the program effectively engaged diverse economic groups (57.4% Below Poverty Line participants), it achieved limited success in gender inclusion (3.3% female participation) and market integration (34.4% success in price negotiations). Key challenges included capacity-building limitations (26%) program structure issues (33%), and market access constraints. The study suggests strengthening community leadership, gender-sensitive programming, and market integration to improve sustainability and support successful scaling.